From MSA to CA : a beginner's guide for transitioning into Colloquial Arabic - Gomaa, Lina; Portland State University. Library; BC Open Textbook Project; BCcampus (Portland State University Library, 2015)
"This book is for students who have studied Modern Standard Arabic (MSA) for one year or more and would like to learn colloquial Arabic basics using their knowledge of MSA. It aims at transitioning learners from Novice Mid level to Intermediate Low through presenting situations useful for living in an Arab country. The book has several features including hyperlinks, practice dialogues with open answers, cultural tips, and more"--BCcampus website.
This work is licensed under the Creative Commons Attribution-NonCommercial CC-BY-NC.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Mode of access: World Wide Web.
This bibliographic record is available under the Creative Commons CC0 "No Rights Reserved" license.
Online version, 2015; title from PDF (viewed on July 11, 2016).
Keywords: Arabic language -- Self-instruction.; Arabic language -- Study and teaching